The effects of radiofrequency energy probe speed and application force on chondrocyte viability - Lu, Y.; Meyer, M. L.; Bogdanske, J. J; Markel, M. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Objective: To determine the thermal effects of monopolar radiofrequency energy (mRFE) on bovine articular cartilage when it was moved at different speeds and using varying application forces.Methods: Thirty-six fresh osteochondral sections divided into two groups (18 sections/group) were used in this study. The first group was tested at three speed rates of mRFE probe (1 mm/sec, 5 mm/sec and 10 mm/sec) at a constant force (50 g) applied to the probe tip. In the second group, three application forces of the probe tip were tested (25 g, 50 g and 75 g) at a constant speed (5 mm/sec) (n=6/test). All tests were performed using a custom-built jig to control the mRFE (Vulcan EAS™) probe during a 20-mm pass on each section. After treatment, viability of osteochondral sections was determined by confocal laser microscopy (CLM) combined with vital cell staining.Results: There were not any significant differences in cartilage thickness of tested osteochondral sections among the different speeds or forces. During the mRFE probe treatments at different speeds, CLM demonstrated that probe application at the speed of 1 mm/ sec caused significantly greater chondrocyte death than at the speeds of 5 and 10 mm/sec, whereas there were no significant differences in chondrocyte death among the variable application forces (p>0.05).Discussion: This in vitro study demonstrated that RFE thermal penetration correlated most closely with probe application speed than application force for this mRFE probe.Clinical relevance: Improper use of mRFE may cause thermal injury on articular cartilage.
Keywords: Chondrocyte; articular cartilage; radiofrequency energy; confocal laser microscopy; thermal chondroplasty